2021
DOI: 10.1186/s12199-021-00934-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of community and school-based sanitation interventions in improving latrine coverage: a systematic review and meta-analysis of randomized controlled interventions

Abstract: Introduction Approximately 1000 children die each year due to preventable water and sanitation-related diarrheal diseases. Six in 10 people lacked access to safely managed sanitation facilities in 2015. Numerous community- and school-based approaches have been implemented to eradicate open defecation practices, promote latrine ownership, improve situation sanitation, and reduce waterborne disease. Objective Given that current evidence for sanitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…It is important to note the risk of reporting bias when relying on surveys with reported sanitation outcomes. 50 , 51 We included cross-validation questions and direct toilet observations to minimize bias, but we do see indications toward reports of better sanitation conditions at baseline and worse conditions at endline, which would have made the deterioration in sanitation conditions appear larger than it truly was. For example, 15% of households at baseline reported that they had never owned a toilet, whereas 28% reported the same at endline ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note the risk of reporting bias when relying on surveys with reported sanitation outcomes. 50 , 51 We included cross-validation questions and direct toilet observations to minimize bias, but we do see indications toward reports of better sanitation conditions at baseline and worse conditions at endline, which would have made the deterioration in sanitation conditions appear larger than it truly was. For example, 15% of households at baseline reported that they had never owned a toilet, whereas 28% reported the same at endline ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Praktik sanitasi dan prilaku sehat adalah dua hal yang tidak dapat dipisahkan, peningkatan kualitas kesehatan bagi siswa berkorelasi dengan sanitasi yang lebih baik pula. Perbaikan sanitasi lingkungan sekolah berdampak positif pada kesehatan siswa dan hasil belajarnya (Igaki et al, 2021). Intervensi seperti program pendidikan kesehatan, dan meningkatkan kebiasaan mencuci tangan telah terbukti mampu mengurangi malnutrisi dan gejala dehidrasi di kalangan siswa (Sangalang et al, 2022).…”
Section: Pendahuluanunclassified
“…For example, Bawankule et al (2017) assessed associations of unsafe CFD with childhood diarrhea in India but did not describe an intervention to address those factors, and this study was therefore excluded. Majorin et al (2019) and Igaki et al (2021) both conducted systematic reviews of interventions that included improving CFD practices among other factors, but reviews were not an included reference type, so these studies were excluded. Gimaiyo et al (2019) and Ellis et al (2020) assessed CFD practices in Kenya, which is not in the Asia-Pacific region.…”
Section: Study Selectionmentioning
confidence: 99%